A framework for integrated terminal airspace design. (May 2019) - Granberg, T.A.; Polishchuk, T.; Polishchuk, V.; Schmidt, C.
ABSTRACT: Route planning and airspace sectorisation are two central tasks in air traffic management. Traditionally, the routing and sectorisation problems were considered separately, with aircraft trajectories serving as input to the sectorisation problem and, reciprocally, sectors being part of the input to the path finding algorithms. In this paper we propose a simultaneous design of routes and sectors for a transition airspace. We compare two approaches for this integrated design: one based on mixed integer programming, and one Voronoi-based model that separates potential "hotspots" of controller activity resulting from the terminal routes. We apply our two approaches to the design of Stockholm Terminal Maneuvering Area.